Dynamical modeling of SAURON galaxies - Cappellari, M; Bosch, R; Verolme, E; Bacon, R; Bureau, M; Copin, Y; Davies, R; Emsellem, E; Krajnovic, D; Kuntschner, H; McDermid, R; Miller, B; et al. (IUTAM, 2018)
We describe our program for the dynamical modeling of early-type galaxies observed with the panoramic integral-field spectrograph SAURON. We are using Schwarzschild's numerical orbit superposition method to reproduce in detail all kinematical and photometric observables, and recover the intrinsic orbital structure of the galaxies. Since catastrophes are the most prominent features in the orbital observables, two-dimensional kinematical coverage is essential to constrain the dynamical models.